The Scientific Miracle in Allah's Words { 'alam Najeal Al'ard Mahada} - Fajr Sobhi Ne'meh, (Islamic Sciences Journal, 2025)
The Great Creator, Glory be to Him, is thanked by His creatures for the gift of paving the Earth, without which man, no matter how great he is, would not have been able to exploit his various powers to overcome problems and pave this land. Therefore, he will be able to live on it and establish any form of civilization, no matter how simple and primitive it is. If paving the earth were not a major matter, the sons of Adam would not have thanked Almighty Allah for it. We must carefully consider the details of this introduction by studying the earth and its relationship to the planets around it, and studying the laws that Almighty Allah has placed on it so that they are compatible with the vital nature of man and his various needs to remain alive. It will multiply and colonize the earth and build its civilizations there until the Doomsday comes. The most important characteristic of soil microorganisms, in addition to the above, is their effective role in completing the carbon and nitrogen cycles in nature, because they are among the most important elements that plants need during their growth stages. The carbon cycle consists of converting carbon dioxide into organic forms and then returning it to its mineral state.